2019
DOI: 10.3390/jcm8040534
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Obstructive Sleep Apnea in Psychiatric Disease

Abstract: Patients with serious psychiatric diseases (major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia and psychotic disorder) often complain about sleepiness during the day, fatigue, low energy, concentration problems, and insomnia; unfortunately, many of these symptoms are also frequent in patients with Obstructive Sleep Apnea (OSA). However, existing data about the clinical appearance of OSA in Psychiatric Disease are generally missing. The aim of our study was a detailed and focused evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…It has been well evidenced that depression, the most common affective disorder found in OSA [16][17][18], is also related to the occurrence and worsening of severe medical conditions such as metabolic and cardiovascular diseases [19], besides being a major contributing factor to non-compliance with OSA treatment [20]. According to a recent study on the prevalence of OSA in psychiatric disease [21], moderate to severe OSA can be found in 72.48% of patients with affective and psychotic disorders, so the consideration of mood disturbances should play an important role in both the evaluation and treatment of this condition. Recent epidemiological studies have also indicated that anxiety may be found in 53.9% of patients with OSA, associated with higher body mass index (BMI) and severity of OSA [11], and once again with poor compliance to OSA therapy [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well evidenced that depression, the most common affective disorder found in OSA [16][17][18], is also related to the occurrence and worsening of severe medical conditions such as metabolic and cardiovascular diseases [19], besides being a major contributing factor to non-compliance with OSA treatment [20]. According to a recent study on the prevalence of OSA in psychiatric disease [21], moderate to severe OSA can be found in 72.48% of patients with affective and psychotic disorders, so the consideration of mood disturbances should play an important role in both the evaluation and treatment of this condition. Recent epidemiological studies have also indicated that anxiety may be found in 53.9% of patients with OSA, associated with higher body mass index (BMI) and severity of OSA [11], and once again with poor compliance to OSA therapy [20].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is linked to increased risk of cardiovascular disorders (Lévy et al, ), metabolic syndrome (Vancampfort et al, ), and diabetes (Stubbs, Vancampfort, De Hert, & Mitchell, ) and thus elevated mortality in BD (Hayes, Miles, Walters, King, & Osborn, ). Obstructive sleep apnoea is diagnosed by overnight sleep assessment in a sleep laboratory, is treated by continuous positive airway pressure, and requires referral to a sleep medicine clinic (preferably one with experience in psychiatric populations; Bastiampillai, Khor, & Dhillon, ; Knechtle et al, ). Similarly, the treatment of DSPS (involving theoretically driven choices around timing of light and melatonin) requires circadian expertise (Sack et al, ) and potentially the involvement of a sleep medicine clinic.…”
Section: Behavioural Strategies In the Context Of Collaborative Care mentioning
confidence: 99%
“…Insightful that sleep plays a role in intellectual and academic attainments 18,19 , OSA has been involved with impaired daytime function and psychiatric symptoms 20 . It has a an impact on road safety and contributes to the burden of road-related morbidity and mortality 21 .…”
Section: Introductionmentioning
confidence: 99%